1991
DOI: 10.1227/00006123-199102000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Hearing Loss from Cerebellopontine Angle Tumors

Abstract: We report two patients who presented with a dramatic recovery from severe sensorineural hearing loss after total surgical removal of cerebellopontine angle tumors (meningioma and jugular foramen neurinoma). The factors that differentiate these “non-acoustic tumors” in relation to the prognosis for hearing are discussed. A surgical approach that maintains the labyrinthine structure and preserves the arachnoid membrane of the superior cerebellopontine angle cistern during tumor removal is stressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…In one deaf patient with a retromeatal tumor (Group 5), even dramatic hearing recovery to normal hearing was observed. Few case reports have previously demonstrated that hearing restoration can occur with CPA meningiomas, even in the face of profound preoperative deficit (4,7,18,35). In our view, these cases show that it is worth attempting hearing preservation in as many patients as possible, even in the case of bad or no clinical preoperative hearing.…”
Section: Discussionmentioning
confidence: 61%
“…In one deaf patient with a retromeatal tumor (Group 5), even dramatic hearing recovery to normal hearing was observed. Few case reports have previously demonstrated that hearing restoration can occur with CPA meningiomas, even in the face of profound preoperative deficit (4,7,18,35). In our view, these cases show that it is worth attempting hearing preservation in as many patients as possible, even in the case of bad or no clinical preoperative hearing.…”
Section: Discussionmentioning
confidence: 61%
“…However, for the petroclival meningiomas a transpetrosal approach has recently proved to us to have major advantages. In the patient with no prospect of useful postoperative hearing, a translabyrinthine approach may be appropriate especially for the tumours involving the internal auditory meatus11 although it must always be remembered that hearing may occasionally improve or even return to normal after the resection of non-acoustic cerebellopontine angle tumours22 23 and destructive approaches must therefore be used selectively.…”
Section: Discussionmentioning
confidence: 99%
“…We do not favor sacrifice of the labyrinth to gain exposure, 29 because improvements in hearing have been reported after removal of these tumors. 10,28,32,36,37 Because schwannomas within the jugular foramen tend to displace the jugular bulb posteriorly, the suprajugular approach allows the surgeon to remove the tumor without opening the wall of the bulb.…”
Section: Neurosurg Focus / Volume 17 / August 2004mentioning
confidence: 99%